Exploring mHealth Participation for Emergency Response Communities - David G. Schwartz (Australasian Journal of Information Systems, 2017)
We explore the challenges of participation by members of emergency response communities who share a similar condition and treatment, and are called upon to participate in emergency events experienced by fellow members. Smartphones and location-based social networking technologies present an opportunity to re-engineer certain aspects of emergency medical response. Life-saving prescription medication extended in an emergency by one individual to another occurs on a micro level, anecdotally documented. We illustrate the issues and our approach through the example of an app to support patients prone to anaphylaxis and prescribed to carry epinephrine auto-injectors. We address unique participation challenges in an mHealth environment in which interventions are primarily short-term interactions which require clear and precise decision-making and constant tracking of potential participants in responding to an emergency medical event. The conflicting effects of diffused responsibility and shared identity are identified as key factors in modeling participation.